Interleukin-8 is increased in chronic kidney disease in children, but not related to cardiovascular disease - Tunçay,Seçil Conkar (2021)
Abstract Introduction: In this study, we aimed to detect the cytokine that is involved in the early stage of chronic kidney disease and associated with cardiovascular disease. Methods: We included 50 patients who were diagnosed with predialytic chronic kidney disease and 30 healthy pediatric patients in Ege University Medical Faculty Pediatric Clinic, İzmir/Turkey. Interleukin-8 (IL-8), interleukin-10 (IL-10), interleukin-13 (IL-13), and transforming grow factor-β1 (TGF-β1) levels (pg/mL) were measured by ELISA. Carotid-femoral pulse wave velocity (PWV), augmentation index (Aix), carotid intima media thickness (cIMT), and left ventricular mass index (LVMI) were evaluated as markers of cardiovascular disease. The presence of a cardiovascular disease marker was defined as an abnormality in any of the parameters (cIMT, PWV, Aix, and left ventricular mass index (SVKI)). The patient group was divided into two groups as with and without cardiovascular disease. Results: Mean Aix and PWV values were higher in CKD patients than controls (Aix: CKD 32.8±11.11%, healthy subjects: 6.74±6.58%, PWV CKD: 7.31±4.34m/s, healthy subjects: 3.42±3.01m/s, respectively; p=0.02, p=0.03). The serum IL-8 levels of CKD were significantly higher than of healthy subjects 568.48±487.35pg/mL, 33.67±47.47pg/mL, respectively (p<0.001). There was no statistically significant difference between IL-8, IL-10, IL-13, TGF-1, in CKD patients with and without cardiovascular disease (p> 0.05). Discussion: IL-8 is the sole cytokine that increases in pediatric patients with chronic kidney disease among other cytokines (IL-10, IL-13 and TGF-β1). However, we did not show that IL-8 is related to the presence of cardiovascular disease.